The Eleven Plus Legacy - De Lisle, Jerome (Daily Express, 2009)
This article seeks to evaluate the legacy of the Eleven Plus Examination in the English-speaking Caribbean, and questions the retention of selection at eleven plus
Keywords: Eleven Plus Examination; Common Entrance Examination; Secondary schools; Entrance examinations; Competitive selection; History of education; Caribbean